ANALISIS PENERIMAAN PENGGUNA DALAM PENERAPAN ERP ATAS TEMUAN AUDIT INTERNAL PADA PT PERKEBUNAN NUSANTARA III ( PERSERO) - Eka Christine Rebeca Simanjuntak (ABIS: Accounting and Business Information Systems Journal, 2019)
ABSTRACT The research aimsto analyze the significant factors that influence the staff acceptance process in PT Perkebunan Nusantara III (Persero) through the implementation of enterprise resource planning (ERP) system. The conceptual framework was developed through the unified theory of acceptance and use of technology (UTAUT) model. The advancement of technology serves as an important feature in the company’s plan to improve their business competition level and to meet the growing users’ expectation. This research employed the mixed method approach. The quantitative data were obtained through closed-ended questionnaires from 127 users. The quantitative data were analyzed using the SPSS 21. Meanwhile, the qualitative data were collected through deep interviews with four users.             The research results indicate that performance expectation, effort expectation, and social influence have positive contributions to behavioral intention. Meanwhile, the facilitating conditions have negative contributions to behavioral intention. In addition, the research also indicated that behavioral intention has significant influence to the users’ behavior. Qualitative data analysis showed that the aspects that might influence the users’ expectation in implementing such system are educational background, age, working period, and topographic condition.